2020
DOI: 10.1002/fsn3.1504
|View full text |Cite
|
Sign up to set email alerts
|

Ionic strength and hydrogen bonding effects on whey protein isolate–flaxseed gum coacervate rheology

Abstract: Whey protein isolate (WPI) was mixed with anionic flaxseed (Linum usitatissimum L.) gum (FG), and phase transition during coacervate formation was monitored. Effects of ionic strength and hydrogen bonding on coacervation of WPI‐FG system and corresponding rheological properties were investigated. During coacervate formation, structural transitions were confirmed by both turbidimetry and confocal laser scanning microscopy. Increasing ionic strength with sodium chloride (50 mM) decreased optical density (600 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…However, the G ′ and G ″ values of WFL 0.6 + NaCl mixtures were obviously higher than those of WF + NaCl mixtures. These were in good accordance with the result of Liu et al (2020) that the G ′ and G ″ values of whey protein isolate‐flaxseed gum coacervates decreased after the addition of NaCl. This may be due to the electrostatic screening effects of NaCl that can weaken the gluten network structures formed by dough and AG.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, the G ′ and G ″ values of WFL 0.6 + NaCl mixtures were obviously higher than those of WF + NaCl mixtures. These were in good accordance with the result of Liu et al (2020) that the G ′ and G ″ values of whey protein isolate‐flaxseed gum coacervates decreased after the addition of NaCl. This may be due to the electrostatic screening effects of NaCl that can weaken the gluten network structures formed by dough and AG.…”
Section: Resultssupporting
confidence: 92%
“…As for the dough–AG mixtures, both hydrogen‐bonding and electrostatic interactions might be predominant between dough and AG. Generally, hydrogen‐bonding interactions might be weaker than electrostatic interactions (Liu et al, 2020). Thus, WFL 0.6 showed looser networks compared with WFA 0.6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have reported higher bioactivity for essential oils at acidic pH. Because, at low pH, essential oils are more hydrophobic and will be passed through the cell membranes easily (Liu et al., 2020). Gelatin‐pectin solutions dissolved in acetic acid solution display low Newtonian behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Non‐starch polysaccharides like galactomannans have been used in food industries for stabilizing foams and emulsions through hydrogen bonds or hydrophobic interactions (Li & de Vries, 2018; Wijaya et al., 2019). The most prominent interactions between proteins and polysaccharides are electrostatic in nature and are formed between the positively charged group of proteins and the negatively charged anionic polysaccharides (Bertsch et al., 2019; Iqbal et al., 2019; Liu et al., 2020). Soluble complexes are formed between WPI and galactomannan at neutral pH with better foam stability due to the higher viscosity of the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%